2022
DOI: 10.3389/fcvm.2022.824561
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of Serum Bone Turnover Markers With Metabolic Syndrome Components and Carotid Atherosclerosis in Patients With Type 2 Diabetes Mellitus

Abstract: ObjectiveThis study aimed to investigate the association of serum bone turnover markers (BTMs) with metabolic syndrome components and carotid atherosclerosis in patients with type 2 diabetes mellitus (T2DM).MethodsWe performed a cross-sectional based study in T2DM populations. Serum BTMs including N-terminal osteocalcin (N-MID), β-cross-linked C-telopeptide of type I collagen (β-CTX), and procollagen type I N-terminal propeptide (PINP) were measured by immunoassay method. Carotid artery intima-media thickness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…A series of studies have reported inverse associations between TG levels and bone turnover markers. [34][35][36] Li et al 34 found that hypertriglyceridaemia was negatively associated with N-MID osteocalcin, β-CTX and P1NP after adjusting for potential confounders, but no significant association was found between serum BTMs and HDL-C in patients with T2D, supporting our conclusion. Liu et al 35 reported that TG levels were negatively correlated with OC or β-CTX levels in young and middle-aged male patients with T2D.…”
supporting
confidence: 76%
“…A series of studies have reported inverse associations between TG levels and bone turnover markers. [34][35][36] Li et al 34 found that hypertriglyceridaemia was negatively associated with N-MID osteocalcin, β-CTX and P1NP after adjusting for potential confounders, but no significant association was found between serum BTMs and HDL-C in patients with T2D, supporting our conclusion. Liu et al 35 reported that TG levels were negatively correlated with OC or β-CTX levels in young and middle-aged male patients with T2D.…”
supporting
confidence: 76%
“…CRP is an important inflammatory mediator; when its levels are high, it can damage blood vessels and cause lipid deposition in the arterial intima, which leads to the occurrence of atherosclerosis (20). TNF-α, as a proinflammatory factor, can promote the secretion of IL-6, cause damage to endothelial cells, cause thrombosis, and lead to blood vessel stenosis and occlusion (21).…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Serum level of OC was reported to be highly associated with T2DM risk, and OC was confirmed to be an independent factor for macrovascular complications in T2DM patients. 18,19 However, few comprehensive analyses have been performed to clarify the association of BTMs and MVCs with T2DM patients in China. BTMs are hypothesized to be potential biochemical indicators of hyperglycemia and microcirculatory dysfunction.…”
Section: Introductionmentioning
confidence: 99%